The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1016/s0022-5347(17)39012-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pinacidil and Cromakalim (BRL 34915) On Bladder Function in Rats with Detrusor Instability

Abstract: Normal rats as well as rats with bladder hypertrophy secondary to outflow obstruction were investigated cystometrically before and after administration of the potassium channel openers pinacidil or cromakalim one mg./kg. orally. In normal rats cromakalim decreased micturition pressure by 15 +/- 6%. A diminished micturition pressure was also seen after pinacidil (by 18 +/- 8%) but this did not achieve statistical significance. Further, no clear-cut effects on bladder capacity, residual volume, basal bladder pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 18 publications
4
40
0
Order By: Relevance
“…Although this observation is consistent with the preclinical efficacy results in animal models (Malmgren et al, 1989), in the absence of placebo-controlled and definitive clinical data, it is thought that cromakalim and subsequent analogs lack sufficient bladder selectivity relative to the vascular effects. Consequently, further clinical proof of principle for KCOs for bladder overactivity mandates a compound with improved selectivity.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Although this observation is consistent with the preclinical efficacy results in animal models (Malmgren et al, 1989), in the absence of placebo-controlled and definitive clinical data, it is thought that cromakalim and subsequent analogs lack sufficient bladder selectivity relative to the vascular effects. Consequently, further clinical proof of principle for KCOs for bladder overactivity mandates a compound with improved selectivity.…”
supporting
confidence: 73%
“…Urinary bladder smooth muscle, unlike arterial smooth muscle, exhibits action potentials and phasic myogenic activity. Previous studies have shown that KCOs can effectively suppress spontaneous contractions in human urinary bladder (Wammack et al, 1994), guinea pig bladder (Fujii et al, 1990;Hashitani et al, 1996), or hypertrophied rat bladder with instability (Malmgren et al, 1989). In the present study, a comparison of the IC 50 values to suppress spontaneous phasic activity showed that A-278637 is 5-to 10-fold more potent compared with both ZD6169 and WAY-133537.…”
Section: Discussionsupporting
confidence: 53%
“…They also depress contractions induced by electrical stimulation, carbachol, and low, but not high external K' concentrations (Anderson, 1993). The KC channel openers were particularly effective in hypertrophic rat bladder muscle in vitro (Malmgren et al 1990) and suppressed bladder hyperactivity in rats with bladder outflow obstruction without affecting bladder emptying (Malmgren et al 1989).…”
Section: Potassium Channelsmentioning
confidence: 97%
“…Cromakalim abolishes spontaneous bladder contractions in pigs [5], rats [8] and rabbits [9] with bladder instability, with little change in other urodynamic variables. Cromakalim also lowers blood pressure in pigs when administered in doses that suppress the unstable contractions [5].…”
Section: Introductionmentioning
confidence: 95%